A bibliometric analysis on halal cosmetics over twenty years - Azmi, Nor Azrini Nadiha; Mohd Noor, Nurul Auni; Elgharbawy, Amal A.M. (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2021)
Purpose – Halal cosmetics area is progressively increasing these days. This bibliometric analysis is intended to systematically evaluate the research to brief researchers about the trend of halal cosmetics field. This paper also discloses the limitations of the studies in the area. Design/methodology/approach – This paper adopted bibliometric and network analysis to evaluate the research area. A total of 82 documents obtained from the Scopus database are extracted and analysed. Findings – The paper reports the type of documents available, the years published, authorship and geographical distribution of the published documents in the halal cosmetics area. From the keyword analysis, it is found that the most used words are halal cosmetics, halal, cosmetics, purchase intention, Malaysia, and Islamic marketing. Research limitations/implications – This bibliometric study is conducted using Scopus database; however, Scopus might possibly omit some publications, thus, authors might not report the missing studies. Halal cosmetics are still in the early years of publications, and only 82 published documents were analysed in the study. Originality/value – There is no study reported on the network analysis and bibliometric study techniques in the area of halal cosmetics.